An observational study on post-operative hemoglobin level in patients undergoing total hip replacement with fracture neck of the femur with and without drain - Ghimire, Kathit Raj; Paudel, Krishna Prasad; Bishta, Rishi (Asian Journal of Medical Sciences, 2022)
Background: The neck of femur fracture is a major public health problem due to ever increasing aging population. Its incidence has drastically increased forthe past few decades. Total hip replacement (THR) is the most common treatment option for displaced fracture neck of femur in high demanding patients who is cognitively intact, independently mobile, and active. Drains have been used with varying success in orthopedic surgery for many years. There are several studies done regarding the utility of drain with conflicting results. Aims and Objectives: To observe the pattern of fall in hemoglobin (Hb) in post-operative patients of fractured neck of the femur with and without drain undergoing THR. Materials and Methods: Observational study was conducted in admitted patients with Fracture Neck of Femur who will be undergoing THR with (cases) and without drain(controls). Pre-operative Hb, Post-operative Hb from day 1 to 5, Length of Hospital Stay, mobilization were taken into consideration for both arms. Results: Among 35 cases studied in each arm,45 were male and 25 were female with male: female ratio of 1.8:1.Maximum number of patients allocated in our study falls in the 60–65 years group (68.58%) followed by the age group of 66–70 years(11.42%) with least number in the age group of 80 years or more (2.84%).Average pre-operative Hb of patients with drain group was 10.6 gm% and non-drain group was 10.2 gm %.Post-operative Hb fall was observed up to first three POD.Mean hospital stay of patients in CSD was 10.9 days as compared to no CSD which was 8.4 days P=0.000*. Mean day of mobilization of patients in CSD was 1.9 days s compared to no CSD which was 1.8 days P=0.291. Conclusion: This study showed keeping drain has more blood less as compared to non drained group.Similarly, CSD had more hospital stay as compared to no CSD but there was no any association with day of mobilization in both arms.